Trace elemental analysis of Anti-Jaundice medicinal plants of Telangana using EDXRF technique. (2021) - Jyothsna, S.; Manjula, G.; Sammaiah, D.; Nageswara Rao, A.S.
Abstract: A quantitative trace elemental concentration was evaluated in various species of medicinal plants using EDXRF-spectrometer. It is non-destructive, multi-element, and high sensitive analytical technique. EX-3600 spectrometer was used for quantitative and quantitative determination of major, minor and trace elements in chosen medicinal plants and data analysis was carried out by nEXT software. Accuracy of the present results was checked by SRM values of NIST 1515Apple leaf. Thirteen elements like, P, S, Cl, K, Ca, Mn, Fe, Cu, Zn, Se, Br, Rb and Sr were determined and their concentrations were measured. From the present results it can be observed that, the elements P, S, Cl, K and Ca were found at higher level and remaining elements were found at lower level. The result of the present study shows good agreement with in the standard values of NIST 1515. The toxic or poisonous elements such as As, Pb, Co, V and Hg were not found in present selected medicinal plants. The elemental concentration of Fe, Cu, Zn, Mn and Se were found at appreciable level. These elements are essential in metabolism and required development, improvement and progressively significant for prevention and mitigate of different diseases including hepatitis and jaundice.